Responses of Litter Decomposition and Nutrient Dynamics to Nitrogen Addition in Temperate Shrublands of North China - Zhang, Jianhua; Li, He; Zhang, Hufang; Zhang, Hong; Tang, Zhiyao (Frontiers in Plant Science, 2021)
Plant litter decomposition is a crucial ecosystem process that regulates nutrient cycling, soil fertility, and plant productivity and is strongly influenced by increased nitrogen (N) deposition. However, the effects of exogenous N input on litter decomposition are still poorly understood, especially in temperate shrublands. In order to investigate the responses of Vitex negundo and Spiraea trilobata litter decomposition to N addition, we conducted a field experiment in Vitex and Spiraea shrublands located on Mt. Dongling in Beijing, North China. Four N treatment levels were applied: control (N0; no N added), low N (N1; 20 kg•N•ha-1•year-1), moderate N (N2; 50 kg•N•ha-1•year-1), and high N (N3; 100 kg•N•ha-1•year-1). N addition increased the amount of remaining N in the two litter types but had no effect on the remaining mass, C or P. N treatment did not affect the decomposition rate constant k of either litter type. Nitrogen addition had no effect on litter decomposition in temperate shrublands. The neutral effect of N addition on litter decomposition may be primarily explained by the low temperatures and P limitation at the site as well as the opposing effects of the exogenous inorganic N that exogenous N inhibits lignin degradation but promotes the decomposition of readily decomposed litter components. These results suggest that short-term N deposition may have a significant impact on N cycling but not C or P cycling in such shrub ecosystems.